Assessment of Microsatellite Markers for Parentage Testing in Jersey Crossbred Cattle in Tamil Nadu: Life Sciences-Molecular Genetics - P, Hepsibha; S M K, Karthickeyan; V, Judia Harriet Sumathy (International Journal of Life Science and Pharma Research, 2022)
A study was aimed to evaluate a set of polymorphic microsatellite markers for their efficiency in testing parentage in Jersey crossbred cattle available in Tamil Nadu. The objective of validation was based on the criteria such as polymorphism information content, various genetic diversity parameters and the ability of markers to exclude the wrong parent. A total of 21 microsatellite markers were included to verify the parentage in 24 Jersey crossbred trios (comprising 24 dams, 24 progenies and 2 sires). The microsatellite loci were amplified using fluorescently labelled primers by multiplex PCR and fragment analysis was done through capillary electrophoresis using automated DNA analyzer. Statistical analyses were done using Pop gene version 1.31, CERVUS 3.0.7 and GENALEX 6.503 software programs. The number of alleles for the markers utilized in the study ranged from 4 (ILSTS11) to 12 (INRA23 and TGLA122) with an overall mean of 8.0952 ± 0.47 alleles per locus. The markers also exhibited high expected heterozygosity (He) and polymorphism information content (PIC) ranging from 0.6362 (ETH3) to 0.8629 (SPS115) with a mean of 0.7681 ± 0.013 and 0.592(ETH3) to 0.83(CSSM66) with a mean of 0.7256±0.014 respectively, signifying them to be highly informative. Low overall probability of identity (PI) of 0.0943 ± 0.008 and high overall probability of exclusion (PE) of 0.9619±0.02 with the increasing locus combinations were observed. The probability of exclusion was cent per cent (PE=1.0000) when a combination of 8 markers were used with one known parent and a combination of 12 markers when excluding a putative pair, suggesting the efficacy and suitability of the markers used in the study for parentage testing on Jersey crossbreds of Tamil Nadu.